Improving Geriatric Care Processes on Two Medical-Surgical Acute Care Units: A Pilot Study. Issue 1 (January 2019) - Booth, Katrina A.; Simmons, Emily E.; Viles, Andres F.; Gray, Whitney A.; Kennedy, Kelsey R.; Biswal, Shari H.; Lowe, Jason A.; Xhaja, Anisa; Kennedy, Richard E.; Brown, Cynthia J.; Flood, Kellie L.
Abstract : ABSTRACT: The Acute Care for Elders (ACE) Unit model improves cognitive and functional outcomes for hospitalized elders but reaches a small proportion of patients. To disseminate ACE Unit principles, we piloted the "Virtual ACE Intervention" that standardizes care processes for cognition and function without daily geriatrician oversight on two non-ACE units. The Virtual ACE Intervention includes staff training on geriatric assessments for cognition and function and on nurse-driven care algorithms. Completion of the geriatric assessments by nursing staff in patients aged 65 years and older and measures of patient mobility and prevalence of an abnormal delirium screening score were compared preintervention and postintervention. Postintervention, the completion of the assessments for current functional status and delirium improved (62.5% vs. 88.5%, p < .001) and (4.2% vs. 96.5%, p < .001). In a subsample analysis, in the postintervention period, more patients were up to the chair in the past day (36.4% vs. 63.5%, p = .04) and the prevalence of an abnormal delirium screening score was lower (13.6% vs. 4.8%, p = .16). The Virtual ACE Intervention is a feasible model for disseminating ACE Unit principles to non-ACE Units and may lead to increased adherence to care processes and improved clinical outcomes. Abstract : Supplemental Digital Content is Available in the Text.